2013
DOI: 10.5713/ajas.2013.13060
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Milk Supplemented with Peanut Sprout Extract Microcapsules during Storage

Abstract: This study was carried out to investigate the physicochemical and sensory properties of milk with added powdered peanut sprout extract microcapsules (PPSEM) during the storage at 4°C for 16 d. The size of PPSEM varies from 3 to 10 μm as observed by the scanning electron microscopy (SEM). The pH values of all samples ranged from 6.8 to 6.6 during the storage. Release of resveratrol for 0.5 and 1% PPSEM addition was about 0.89 μl/ml and TBARS value found to lower during storage of 16 d. The a* and b* color value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
3
1
Order By: Relevance
“…2 ). Contrary to our results, Lee et al . (2013) reported proportional increase in TBARS value with increasing concentrations of powdered peanut sprout extract microcapsulessupplemented milk during storage.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…2 ). Contrary to our results, Lee et al . (2013) reported proportional increase in TBARS value with increasing concentrations of powdered peanut sprout extract microcapsulessupplemented milk during storage.…”
Section: Resultscontrasting
confidence: 99%
“…(2013) reported slight increase in the pH of cinnamon oil milk with increasing cinnamon oil concentration; however, no significant difference was reported during storage. According to Lee et al . (2013) , peanut sprout extract was microencapsulated using water in oil in water (W/O/W) system by spray dryer to apply in milk.…”
Section: Resultsmentioning
confidence: 99%
“…Studies of caffeic acid enrichment in peanut sprouts [4] have shown that total phenolics and flavonoids increase greatly after germination [5] . Lee studied microcapsules containing powdered peanut sprout extract placed into milk or yogurt [6] , [7] , [8] , and Yang studied the anti-allergenic effects of peanut sprouts [9] .…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that the low concentrations (0.25 and 0.50%, w/v) could be used to produce powdered peanut sprout extract microcapsules (PPSEM)-supplemented yoghurt without significant adverse effects on the physicochemical and functional properties (Lee et al, 2013c). Meanwhile, the low concentrations of the microcapsules (0.5 and 1.0%, w/v) could be suitable to produce the microcapsule-supplemented milk without significant adverse effects on the physicochemical and sensory properties of milk (Lee et al, 2013b). Ahn et al (2012) compared nanopowdered peanut sprout (NPPS) and powdered peanut sprout-added yogurt on its physicochemical and sensory properties during storage.…”
Section: Introductionmentioning
confidence: 99%